Post-acute sequelae of SARS-CoV-2 Delta variant infection: A report of three cases in a single family (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
Coronavirus disease 2019 (COVID-19) is caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) that has resulted in global pandemic and crisis in health care system. Several studies have focused only on hospitalized patients with 30 to 90 days after one cycle of illness but post-acute sequelae of COVID-19 existing even after a year remains unclear. Moreover, long-term sequelae in outpatients have not been documented and henceforth myriad clinical sequelae in long haulers continue to evolve. In this study, we report three cases represents a single family presenting several post-acute sequelae one after the other extending beyond one year of recovery. To our knowledge such a case series has not been reported in earlier studies. Herein, we present the sequelae in various organs namely neuropsychiatric (tinnitus, anxiety, depression, insomnia, and posttraumatic stress disorder, cognitive decline), cardiovascular (tachycardia, bradycardia), gastrointestinal (appendicitis) and Dermatologic (erythematous rash and acne) besides ophthalmic manifestations (conjunctivitis and dry eyes) in Long-COVID-19 and recommend management strategies.